고유수용성 감각과 신체 소유감 - 윤샤론(Sharon Yoon) (인지과학, 2023)
This paper aims to examine how proprioception provides a sense of ownership over one's body and physical actions. Proprioception is a sense that relies on somatic interoceptors rather than exteroceptors that receive external stimuli and has epistemic importance of knowing the presence, location, and movement of bodily parts. In this paper, I will argue that Shoemaker's principle, "Immunity to Error through Misidentification (IEM)" can be applied to proprioception by focusing on one of the intrinsic features of proprioception: First-Person Perspective. I will advocate the following two arguments by defeating each of Marcel's pathological counter-examples in turn. Proprioception is infallible in that it provides a sense of ownership over one's body and physical actions. Second, proprioception is indispensable for the sense of ownership of one's body and physical actions. 이 논문의 목적은 고유수용성 감각(proprioception)이 자신의 신체와 신체적 행위(physical action)에 대해 소유감(sense of ownership)을 부여하는 것을 검토하는 데 있다. 고유수용성 감각은 외부 자극을 받아들이는 외수용기가 아닌 신체 내부의 신경조직인 내수용기에 의존하는 감각으로, 신체 부분(bodily parts)의 존재, 위치, 움직임을 아는데 있어 인식적으로 중요하다. 본고에서는 고유수용성 감각의 중요한 특징 중 하나인 일인칭성에 주목하여 슈메이커의 '오식별 오류에의 면역성Immunity to Error through Misidentification(이하 IEM)'이 고유수용성 감각에 적용할 수 있음을 논증하고자 한다. 필자는 다음 두 가지 주장을 비판적으로 검토하고 심리철학자 마르셀이 제기하는 병리적 반증사례를 차례대로 모두 격파함으로써 두 주장을 공고히 한다. 첫째, 고유수용성 감각은 내 신체와 신체적 행위에 관한 소유감을 제공한다는 점에서는 오류불가능하다. 둘째, 고유수용성 감각은 내 신체와 신체적 행위의 소유감을 위해 필수불가결하다.